The Effect of the Mobile Correspondent Strategy on the Achievement of Students of the College of Basic Education / Department of Science in the practical Subject of Algae and Fungi - et. al., Rania Mohammed Jassam Hammadi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to identify the impact of the strategy of the mobile correspondent on the achievement of students of the College of Basic Education / Department of Science in the practical subject of algae and fungi . To achieve the goal of the research, the following null hypotheses were developed: 1- There is no statistically significant difference at the level of (0.05) between the average scores of the experimental group students who studied according to the mobile correspondent strategy and the average scores of the control group students who studied according to the usual method in the practical test of algae and fungi. To achieve the goal of the research and its hypotheses, the researcher adopted the experimental design with two groups of experimental and control, one of them controlling the other partial control and those with a post-test to measure achievement and positive thinking. The current research community is represented by all the students of the third stage / Department of Science / Branch of Life Sciences / Colleges of Basic Education in Iraq for the academic year (2020-2021), The researcher chose the third-stage students of the Science Department / Life Sciences Branch in the College of Basic Education / Al-Mustansiriya University as an intentional sample, as the number of its members reached (83) students distributed between two classrooms (A and B).